ETUDE DES STRUCTURES, PROPRIETES ELECTRONIQUES ET DES INTERACTIONS DU COMPLEXE D’INCLUSION PAR LA METODE DFT - Amina Gouasmia (My University, 2023)
In this work, the structure and stability of the inclusion complex formed by N-(5-ethyl-1,3,4-thiadiazole-2-yl)-4-nitrobenzamid and 2-Hydroxylpropyl-β-cyclodextrin (2-HP-β-CD) were studied theoretically by computational methods in the gas phase and in the solvent . These models were geometrically optimized using the DFT functionality: B3LYP with a 6-31 G base. The geometries of these complexes were optimized and the results were analyzed and compared. HOMO and LUMO energies and the global chemical reactivity descriptors were computed. The obtained results clearly indicate that the formed complexes are energetically favored. ----------------------------------------------------------------------------- في هذا العمل، تمت دراسة بنية و استقرار معقد الاحتواء الذي شكله N-(5-ethyl-1,3,4-thiadiazole-2-yl)-4-nitrobenzamide مع 2-hydroxypropy1-β cyclodextrine من الناحية النظرية بواسطة حسابات كيمياء الكم في الفراغ و في الماء . تم تحسين الأشكال الهندسية لهذه المجمعات و تم تحليل النتائج و مقارنتها تم تحسين حساب طاقات HOMOو LUMO وواصفات التفاعل الكيميائي العالمية تم تحسين هذه النماذج هندسيا باستخدام وظائف DFT :B3LYP بقاعدة 6-31 G تشير النتائج التي تم الحصول عليها بوضوح إلى أن المجمعات التي تكيلها مفضلة من حيث الطاقة. ----------------------------------------------------------------------------- In this work, the structure and stability of the inclusion complex formed by N-(5-ethyl-1,3,4-thiadiazole-2-yl)-4-nitrobenzamid and 2-Hydroxylpropyl-β-cyclodextrin (2-HP-β-CD) were studied theoretically by computational methods in the gas phase and in the solvent . These models were geometrically optimized using the DFT functionality: B3LYP with a 6-31 G base. The geometries of these complexes were optimized and the results were analyzed and compared. HOMO and LUMO energies and the global chemical reactivity descriptors were computed. The obtained results clearly indicate that the formed complexes are energetically favored.